2010
DOI: 10.1016/j.limno.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, diversity and succession of aquatic Coleoptera and Heteroptera in a cluster of artificial ponds in the North German Lowlands

Abstract: a b s t r a c tOur study describes and evaluates environmental influences on assemblages of aquatic Coleoptera and Heteroptera in artificial ponds situated near Lake Steinhude in Lower Saxony (Germany). We determined temporal dynamics and colonization patterns for 14 ponds of different age. In total, we recorded 4941 individuals that represented 87 species of aquatic beetles and bugs. Between 30 and 40 species were found in most of the ponds. Heteropteran species of the families Corixidae and Notonectidae acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 15 publications
10
59
0
2
Order By: Relevance
“…This accords with e.g. De Szalay and Resh (2000), Herrmann et al (2000), Williams et al (2007), Bloechl et al (2010). Chironomids also appeared early in Skälby Dämme, confirming Barnes (1983), Layton and Voshell (1991), Herrmann et al (2000), Hov and Walseng (2003), and Ekologgruppen (2010), whereas Oertli and Lachavanne (1995) found them to be "particularly slow colonisers".…”
Section: Invertebratessupporting
confidence: 84%
See 1 more Smart Citation
“…This accords with e.g. De Szalay and Resh (2000), Herrmann et al (2000), Williams et al (2007), Bloechl et al (2010). Chironomids also appeared early in Skälby Dämme, confirming Barnes (1983), Layton and Voshell (1991), Herrmann et al (2000), Hov and Walseng (2003), and Ekologgruppen (2010), whereas Oertli and Lachavanne (1995) found them to be "particularly slow colonisers".…”
Section: Invertebratessupporting
confidence: 84%
“…This initial occurrence may be related to their special capacity of flight behaviour in combination with well-adapted lifecycles (Bilton et al, 2001). That beetles, and often dytiscids, often form the most species-rich early colonising group was also found by Fairchild et al (2000), Lundkvist (2003), Williams et al (2007), and Ekologgruppen (2010), while Bloechl et al (2010) found that aquatic coleopterans predominate in older ponds.…”
Section: Invertebratesmentioning
confidence: 91%
“…Other insect groups such as the Hemiptera (e.g. Naucoris, Agraptocorixia, Sigara and Anisops) prefer open water (Bloechl et al 2010;Mereta et al 2012). In our study, these taxa were also more abundant in less vegetated wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Force 1981;Smith 1982;Kaufman 1983), it can also be tested in man-made aquatic habitats, e.g. marshy wetlands (Levin et al 1996;Herrmann et al 2000), pond clusters (Seabloom and Van Der Valk 2003;Bloechl et al 2010) or reservoirs (Voshell and Simmons 1984;Bass 1992;Koskenniemi 1994). In turn, the study of primary succession has generated theories on mechanisms by which communities are assembled, including the relative role of deterministic and stochastic pathways (Milner et al 2008).…”
Section: Introductionmentioning
confidence: 99%